2016
DOI: 10.1038/nutd.2016.37
|View full text |Cite
|
Sign up to set email alerts
|

Long-term treatment with metformin in obese, insulin-resistant adolescents: results of a randomized double-blinded placebo-controlled trial

Abstract: Background:As adolescents with obesity and insulin resistance may be refractory to lifestyle intervention therapy alone, additional off-label metformin therapy is often used. In this study, the long-term efficacy and safety of metformin versus placebo in adolescents with obesity and insulin resistance is studied.Methods:In a randomized placebo-controlled double-blinded trial, 62 adolescents with obesity aged 10–16 years old with insulin resistance received 2000 mg of metformin or placebo daily and physical tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 36 publications
2
58
1
1
Order By: Relevance
“…Although the effect of metformin might fade out over time, it remains unclear whether prolonged use (>18 months) of metformin is not effective any more (i.e., children treated with metformin return to their previous BMI-percentile), or whether it will result in persisting lower BMI-values compared to placebo. For the 18-month treatment, the current study showed that the change in BMI upon metformin in daily clinical practice was similar to results as obtained in a RCT after treatment of 18 months [8]. …”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Although the effect of metformin might fade out over time, it remains unclear whether prolonged use (>18 months) of metformin is not effective any more (i.e., children treated with metformin return to their previous BMI-percentile), or whether it will result in persisting lower BMI-values compared to placebo. For the 18-month treatment, the current study showed that the change in BMI upon metformin in daily clinical practice was similar to results as obtained in a RCT after treatment of 18 months [8]. …”
Section: Discussionsupporting
confidence: 81%
“…This small increase in ΔBMI at 18 months was initially preceded by a substantial decrease in ΔBMI in the metformin arm at 9 months, while in the placebo arm of this RCT ΔBMI from baseline to 18 months was found to increase significantly compared to the metformin arm (i.e., ΔBMI +1.17 (−0.26–2.37) kg/m 2 ( p = 0.015)) [8]. In the current study, the course of BMI and BMI-SDS over time in the daily clinical practice group also showed an initial decrease in BMI and BMI-SDS in accordance with the RCT group.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…32,37 Out of included studies, 12 studies were performed in children 17,25,27,28,31,32,39,40,42,[44][45][46]51 and 25 studies in adolescents. [10][11][12][18][19][20][21][22][23][24]26,29,30,[33][34][35][36][37][38]41,43,[47][48][49][50] In addition, six studies were conducted in female participants, 21,26,30,31,44,47 while the others recruited participants from both genders. [10][11][12][17][18]…”
Section: Study Characteristicsmentioning
confidence: 99%